Determination of virulence factors and antibiotic resistances of enterococcus spp. identified from different stages of ripened (classical) white cheese production - Gökmen, Mukadderat; Ektik, Nisanur (Afyon Kocatepe Üniversitesi)
The objective of this research was to determine the presence of virulence genes (asa1, gelE, cylA, ace, esp, hyl and efaA), and vancomycin resistance genes (vanA, vanB, vanC2/C3) and the resistance to some antibiotics of Enterococcus spp. isolates previously identified from different stages of ripened white cheese production. In addition, gelatinase, β-hemolytic and DNase activity, and biofilm formations were examined phenotypically. In this study, efaA in 95.9%, asa1 in 89%, ace in 68.5%, esp in 52.1%, gelE in 78.1%, cylA in 16.4% and hyl in 23.3% of isolates were detected. Also, vanA in 31.5%, vanB in 8.2%, and in vanC2/C3 23.3% resistance genes were determined. β-hemolytic and DNase activity were detected in 23.2% and 16.4% of the isolates, while gelatinase activity and biofilm formation could not be detected phenotypically. Moreover, streptomycin and erythromycin resistances were found in 73.9% and in %43.8 of isolates. As a result, it was concluded that Enterococcus spp. may pose a risk for public health and food safety in terms of their virulence factors and antibiotic resistance. For this reason, it was suggested that the strains to be selected as starter cultures should be used after evaluating their virulence factors and resistance to antibiotics.

Bu çalışmada, daha önce klasik beyaz peynir üretiminin farklı aşamalarından identifiye edilen Enterococcus spp. izolatlarının virülens genleri (asa1, gelE, cylA, ace, esp, hyl ve efaA) ve vankomisin direnç genlerinin (vanA, vanB, vanC2/C3) varlığı ile bazı antibiyotiklere dirençliliklerinin belirlenmesi amaçlandı. Ayrıca jelatinaz, β-hemolitik ve DNase aktiviteleri ile biyofilm oluşumları fenotipik olarak ise incelendi. İzolatların %95,9’unda efaA, %89’unda asa1, %68,4’ünde ace, %52,1’inde esp, %78,1’inde gelE, %16,4’ünde cylA ve %23,3’ünde hyl virülens genleri tespit edildi. Ayrıca %31,5’inde vanA, %8,2’sinde vanB ve %23,3’ünde vanC2/C3 direnç genleri belirlendi. Fenotipik olarak ise izolatların sırasıyla %23,2'sinde ve %16,4'ünde β-hemolitik aktivite ve DNase aktivitesi tespit edilirken, jelatinaz aktivitesi ve biyofilm oluşumu tespit edilememiştir. Bunun yanı sıra izolatların %73,9’unda streptomycin ve %43,8’inde erythromycin direnci saptandı. Sonuç olarak, Enterococcus spp.’nin virülans faktörleri ve antibiyotik direnci açısından halk sağlığı ve gıda güvenliği için risk oluşturabileceği kanaatine varıldı. Bu nedenle starter kültür olarak seçilecek suşların virülens faktörleri ve antibiyotiklere dirençlilik bakımından değerlendirildikten sonra kullanılmaları önerildi.
Olgunlaştırılmış (klasik) beyaz peynir üretiminin farklı aşamalarından izole edilen enterococcus spp.’nin virülens faktörlerinin ve antibiyotik dirençliliğinin belirlenmesi
Keywords: Antibiotic Resistance; Enterococcus spp.; Ripened White Cheese; Virulence Factor; Antibiyotik Direnci; Enterococcus spp.; Klasik Beyaz Peynir; Virülens Faktör